Hybrid Aspen Expressing a Carbohydrate Esterase Family 5 Acetyl Xylan Esterase Under Control of a Wood-Specific Promoter Shows Improved Saccharification - Wang, Zhao; Pawar, Prashant Mohan-Anupama; Derba-Maceluch, Marta; Hedenström, Mattias; Chong, Sun-Li; Tenkanen, Maija; Jönsson, Leif J.; Mellerowicz, Ewa J. (Frontiers in Plant Science, 2020)
Fast-growing broad-leaf tree species can serve as feedstocks for production of bio-based chemicals and fuels through biochemical conversion of wood to monosaccharides. This conversion is hampered by the xylan acetylation pattern. To reduce xylan acetylation in the wood, the Hypocrea jecorina acetyl xylan esterase (HjAXE) from carbohydrate esterase (CE) family 5 was expressed in hybrid aspen under the control of the wood-specific PtGT43B promoter and targeted to the secretory pathway. The enzyme was predicted to deacetylate polymeric xylan in the vicinity of cellulose due to the presence of a cellulose-binding module. Cell-wall-bound protein fractions from developing wood of transgenic plants were capable of releasing acetyl from finely ground wood powder, indicative of active AXE present in cell walls of these plants, whereas no such activity was detected in wild-type plants. The transgenic lines grew in height and diameter as well as wild-type trees, whereas their internodes were slightly shorter, indicating higher leaf production. The average acetyl content in the wood of these lines was reduced by 13%, mainly due to reductions in di-acetylated xylose units, and in C-2 and C-3 mono-acetylated xylose units. Analysis of soluble cell wall polysaccharides revealed a 4% reduction in the fraction of xylose units and an 18% increase in the fraction of glucose units, whereas the contents of cellulose and lignin were not affected. Enzymatic saccharification of wood from transgenic plants resulted in 27% higher glucose yield than for wild-type plants. Brunauer–Emmett–Teller (BET) analysis and Simons’ staining pointed toward larger surface area and improved cellulose accessibility for wood from transgenic plants compared to wood from wild-type plants, which could be achieved by HjAXE deacetylating xylan bound to cellulose. The results show that CE5 family can serve as a source of enzymes for in planta reduction of recalcitrance to saccharification.